PENERAPAN KONSELING INDIVIDU DENGAN PENDEKATAN BEHAVIORAL UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR DARING SISWA SMP DI DESA PENGIN RT I/RW III POPONGAN KARANGANYAR TAHUN 2021 - Putri, Briva Ekapurnamasari (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
The purpose of this research was to find out how is the influence of individual counseling with a behavioral approach to the effectiveness in increasing online learning discipline of junior high school students in Pengin Village RT I/RW III Popongan Karanganyar in 2021. This research was conducted in Pengin Village RT I/RW III Popongan Karanganyar. The subjects of this research were junior high school students, totaling 2 students. The research method used is Counseling Guidance Action Research (PTBK) which is carried out in 2 cycles, each cycle consists of 4 stages, namely, Planning (planning), Action (action), Observation (observation) and Reflection (reflection). The technique of data collection used in this research were observation, interviews, and documentation. From the results of this research it was found that there was an increase in online learning discipline in junior high school students. In the first cycle, the results of learning discipline changed and increased but there were still some indicators that were categorized as less disciplined with a percentage for AD students 60% and RJ students 63.5%. Both students have succeeded in improving their learning discipline but has not increased significantly. Furthermore, in the second cycle, the results showed that the student discipline was a change significantly and it can bee categorized as successful, with discipline for AD students reaching 76.25% and for RJ reaching 77.5%. Yet, both students have achieved indicators in the discipline category so it can be concluded that the implementation of individual counseling with a behavioral approach can improve online learning discipline for junior high school students in Pengin village RT I/RW III Popongan Karanganyar in 2021. Key Words: Individual Counseling, Behavioral Approach, Online Learning Dicipline